Evaluation with applications of strength and compressibility characteristics of soil samples obtained by Shelby tube and split-spoon samplers in comparison with in-situ test results - Polinar, Luzviminda Tiongson; Bergado, Dennes T.; Balasubramaniam, A.S.; Sugimoto, M.; Government of New Zealand (Bangkok : Asian Institute of Technology, 1994)
The main focus of this study are to establish correlations of strength characteristic of Shelby tube and split-spoon samples, and compare the strength and compressibility parameters derived from laboratory and field tests. Furthermore, the derived strength and compressibility parameters were used in the prediction of the stability and settlement of full scale test embankments. Samples from both split-spoon and Shelby tube samplers were tested in unconfined compression and unconsolidated undrained triaxial tests. Three oedometer and three Rowe cell consolidation tests were also performed to determine the compressibility of soil. In the field, four field vane shear tests and two screw plate load tests were conducted. The undrained strength from split-spoon samples are slightly higher than the samples from shelby tube. The ratio between Cv(field} to Cv(lab) ranges from 1. 7 to 11. The Cv values derived from Rowe cell consolidometer are in better agreement to the field values than those derived from the conventional oedometer tests. Moreover, the embankment settlement prediction was performed using the parameters derived from oedometer, Rowe cell, screw plate load tests as well as the Asaoka's graphical method. The Asaoka's graphical method fits best with the actual settlement. The settlement prediction using the derived compressibility parameters from Rowe cell agrees very well with the observed data. Oedometer yielded the most conservative prediction. Furthermore, the UU and corrected field vane undrained strengths are in good agreement with the actual strengths mobilized in the field. The corrected strengths obtained from UC tests gave a reasonable prediction of the factor of safety. Moreover, the corrected UU strengths from split-spoon gave a slightly higher prediction. Other methods from MESRI (1975) and SHANSEP (LADD & FOOT, 1974) were also considered in which both predicted the embankment stability very well.
A thesis submitted in partial fulfillment of the requirements for the degree in Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Soils -- Testing